Development and initial validation of the life skills ability scale for higher education students - Lorcan Cronin; Justine Allen; Paul Ellison; David Marchant; Andrew Levy; Chris Harwood (2019)
This research developed a scale to assess the following life skills in higher education students: teamwork, goal setting, time management, emotional skills, interpersonal communication, social skills, leadership, and problem solving and decision making. Study 1 adapted an existing scale for the purposes of this research and provided evidence for the factorial validity of the new scale with 445 students. Study 2 included 423 students and supported the predictive validity of the scale in relation to students’ psychological well-being, academic self-efficacy/performance, and health-related quality of life. Study 3 provided evidence for the test-retest reliability of the scale with 49 students. All three studies supported the internal consistency reliability of the scale. Combined, these studies suggest that the scale is a valid and reliable measure that researchers, policymakers and educators could use to assess and potentially enhance higher education students’ life skills. Future research directions and uses of the scale are discussed.